Efficient CRISPR/Cas9‐Mediated Mutagenesis in Primary Murine T Lymphocytes. (12th October 2018) - Huang, Bonnie; Johansen, Kristoffer Haurum; Schwartzberg, Pamela L.
Abstract: The ability to alter gene expression directly in T lymphocytes has provided a powerful tool for understanding T cell biology, signaling, and function. Manipulation of T cell clones and primary T cells has been accomplished primarily through overexpression or gene‐silencing studies using cDNAs or shRNAs, respectively, which are often delivered by retroviral or lentiviral transduction or direct transfection methods. The recent development of CRISPR/Cas9‐based mutagenesis has revolutionized genomic editing, allowing unprecedented genetic manipulation of many cell types with greater precision and ease. This article outlines a protocol for CRISPR/Cas9‐mediated mutagenesis in primary T lymphocytes from Cas9 transgenic mice using retroviral delivery of guide RNAs. © 2018 by John Wiley & Sons, Inc.